1993
DOI: 10.1042/bj2910361
|View full text |Cite
|
Sign up to set email alerts
|

Versican gene expression in human articular cartilage and comparison of mRNA splicing variation with aggrecan

Abstract: The chondrocytes in human articular cartilage from subjects of all ages express mRNAs for both of the aggregating proteoglycans aggrecan and versican, although the level of expression of versican mRNA is much lower than that of aggrecan mRNA. Aggrecan shows alternative splicing of the epidermal growth factor (EGF)-like domain within its C-terminal globular region, but there is no evidence for a major difference in situ in the relative expression of this domain with age. At all ages studied from birth to the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 34 publications
2
36
0
1
Order By: Relevance
“…Versican is a large chondroitin sulfate proteoglycan expressed by human fibroblasts. The expression levels of versican are much lower than those of aggrecan in human articular cartilage, although the chondrocytes in human articular cartilage express mRNA for both aggrecan and versican (20). Bovine microarray data revealed that the aggrecan expression in articular cartilage is higher than that in the annulus fibrosus, whereas versican expression in articular cartilage is lower than that in the annulus fibrosus (21).…”
Section: Discussionmentioning
confidence: 96%
“…Versican is a large chondroitin sulfate proteoglycan expressed by human fibroblasts. The expression levels of versican are much lower than those of aggrecan in human articular cartilage, although the chondrocytes in human articular cartilage express mRNA for both aggrecan and versican (20). Bovine microarray data revealed that the aggrecan expression in articular cartilage is higher than that in the annulus fibrosus, whereas versican expression in articular cartilage is lower than that in the annulus fibrosus (21).…”
Section: Discussionmentioning
confidence: 96%
“…Alternative splicing of the EGF and SCR modules in the G3 domain is well established (22)(23)(24)(25)(26) and could have an effect on the interactions of the C-type lectin repeat. Although there are binding studies using full-length proteoglycan (17) or recombinant G3 domains (14,15,20), no thorough investigation of the effects of alternative splicing in the G3 domain has been published.…”
Section: Discussionmentioning
confidence: 99%
“…The other modules of the G3 domains are subject to alternative splicing (22)(23)(24)(25)(26). The expression of the SCR module is variable, but in humans this module is usually present, regardless of age (26). The EGF1 and EGF2 modules are expressed to a lower extent (25-28 and 5-8%, respectively, in humans) (22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The 30 cycles of PCR determined to be in the linear range for GAPDH, aggrecan, and types I and II collagens, included denaturation (958C, 45 s), annealing (588C, 45 s), and extension (728C, 60 s). 20 Similarly, the 30 cycles for type X collagen PCR included denaturation (958C, 60 s), annealing (508C, 60 s), and extension (728C, 5 min). 21 Amplified products were analyzed by electrophoresis on 2% agarose gels and visualized by ethidium bromide staining.…”
Section: Reverse Transcriptase-polymerase Chain Reaction (Rt-pcr)mentioning
confidence: 99%